KAJIAN PENYEBAB STUNTING ANAK USIA 24 - 59 BULAN DIWILAYAH KERJA PUSKESMAS PADANG GELUGUR KABUPATEN PASAMAN - Neila Sulung (Badan Penelitian and Pengembangan (Balitbang), Padang, West Sumatra, Indonesia, 2020)
Stunting is a chronic condition that represent growth retardation due to long-term malnutrition, indicated by a z-score of TB / U less than -2SD. Padang Gelugur is a sub-district located in Pasaman Regency with the highest stunting rate of 27%. The purpose of this study was to determine the factors that caused the incidence of Stunting at the Padang Gelugur health center in Pasaman Regency. Type of analytic descriptive study with cross-sectional design, conducted in April 2019. The population is 1,020 infants. with Multistage random sampling technique and a sample size of 150 infants. Data collection uses questionnaires and anthropometric observations and data analysis includes univariate analysis and bivariate analysis with chi square test. The results of the study obtained the incidence of stunting in infants due to non-exclusive breastfeeding (p = 0.022 and OR = 2.708), lack of food diversity (p = 0.023 and OR = 2.326), and low economic status (p = 0.034 and OR = 3.630. Based on the results above, it was found that a significant relationship between low economic status, non-exclusive breastfeeding, and lack of food diversity with the incidence of Stunting.